Heterogeneous expression and biological function of SOX18 in osteosaroma. Issue 5 (22nd January 2018) - Zhu, Danjie; Yang, Di; Li, Xiaolin; Feng, Fabo
Abstract: Osteosaroma (OS) is a primary bone malignancy and is associated with high morbidity. Sex determining region Y‐box 18 (SOX18) is identified overexpressed in OS. However, the molecular mechanism underlying the biological function of SOX18 in OS is still unclear. The aim of the current study was to determine the SOX18 expression in patients with OS and its effect on tumor cell malignant phenotypes. Our results showed that SOX18 was overexpressed in OS patients from both E‐MEXP‐3628 database and independent samples from our hospital and in OS cell lines. SOX18 silencing significantly induced G0‐G1 phase cell cycle arrest and apoptosis and inhibited U‐2OS cell migration and invasion and cell growth both in vitro and in vivo. However, SOX18 overexpression remarkably promoted 143B cell proliferation, migration and invasion and inhibited cell cycle arrest and apoptosis. The protein expression levels of p53, p21, Bax, Bcl‐2, and Caspase‐3 were also regulated by SOX18. Moreover, SOX18 was found negative correlated with the expression of HERC1, HER2, HERC3, HERC4, HERC5, and HERC6 in OS patients and in OS cells, with the most significant correlation detected in HERC2 expression, which was following found interacted with SOX18 in OS cells. Taken together, our results suggest that SOX18 is overexpressed in OS and plays an important role in proliferation, apoptosis, migration and invasion of OS cells, and may provide a novel and promising therapeutic strategy for OS. Abstract : SOX18 was overexpressed in OS tumor tissues and cell lines, and regulated the proliferation, cell cycle, apoptosis, migration, and invasion of OS cells, which may in part through interacting with HERC2. Therefore, these data suggested that targeting SOX18‐HERC2 interaction provide us a new treatment strategy for OS.